467 EFFICACY OF TRANSCATHETER INTERATRIAL SHUNT DEVICES IN HEART FAILURE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (15th December 2022) - Basile, Christian; Marzano, Federica; Dellegrottaglie, Sarto; Gargiulo, Paola; Abbate, Vincenza; Ambrosio, Antonio; Carbone, Francesca; Dell´aversana, Simona; Esposito, Immacolata; Fierro, Maria Francesca; Perrone-filardi, Pasquale; Paolillo, Stefania
Abstract: Background: In patients affected by heart failure with reduced ejection fraction (HFrEF), pharmacological treatments have been proven to alleviate symptoms and improve prognosis, while no treatment other than sodium-glucose co-transporter-2 inhibitors have demonstrated significant effects in HF with preserved ejection fraction (HFpEF). Left-to-right interatrial shunt devices are now being investigated for left atrial decompression in patients with HF. Objectives: To assess the efficacy of left-to-right interatrial shunt devices (IASD) on soft endpoints in HF patients. Methods: PubMed and Web of Science were searched without restrictions from inception to 28 May 2022 to identify valuable articles. The studies that met the inclusion criteria were analyzed. The prespecified main outcomes were the change from baseline in 6-minute walking distance (6MWD), NYHA class and health-related quality of life (HRQoL). Secondary outcomes were reduction in HF hospitalizations, and echocardiographic and hemodynamic parameters. Results: Ten studies, with a total of 539 patients were included. IASD significantly improved 6MWD of 44.19 m (95% CI: 29.82–58.56 m), decreased NYHA class by 0.89 (95% CI: 1.10–0.67), and improved HRQoL questionnaire by 20.19 points (95% CI: 12.94–27.44) with better results for all outcomes in younger patients and in patients with lower EFs (Figure). Conclusion: The present meta-analysis suggests that IASD are favorable in improving 6MWD, NYHA class, and HRQoL in HF across a wide spectrum of ejection fraction, with better outcomes in younger patients and in patients with lower EFs.